DUAL ROLE OF MAGNESIUM IN MIGRAINE: EFFICACY & SAFETY IN TREATMENT AND PREVENTION—A META-ANALYSIS - Isadora, Eugenia; Kusuma, Hendrawan Chandra; Prathama, Hans Aditya; Ann, Clara (Acta Neurologica Indonesia, 2025)
Introduction: Magnesium deficiency has been associated with migraines, suggesting its potential as a therapeutic intervention. Objective: To assess the efficacy and safety of intravenous (IV) and oral magnesium for the treatment and prevention of migraines in adults. Material and methods: A systematic review following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines was conducted across multiple databases for randomized controlled trials (RCT) involving adult migraine patients treated with IV magnesium (1-2g) for acute attacks or oral magnesium (≥8 weeks) for prevention. Study quality was assessed using the Cochrane Risk of Bias 2 tool, and meta-analysis was conducted with Review Manager 5.4. Result: Twelve trials were included. IV magnesium showed significant benefits for acute migraines, including better headache response (p = 0.02), reduced pain intensity (p = 0.03), and less rescue medication use (p = 0.02). Oral magnesium was as effective as sodium valproate for prevention but showed limited benefits over placebo for attack frequency (p = 0.09). Gastrointestinal side effects were more common with oral magnesium (p = 0.01). Discussion: Magnesium modulates methyl-D-aspartate (NMDA) receptors, preventing excessive calcium influx and cortical spreading depression, which are key in migraine pathophysiology. IV magnesium is effective for acute treatment with a favorable safety profile. Oral magnesium shows potential for migraine prevention, with efficacy similar to sodium valproate, though gastrointestinal side effects limit its use. Conclusion: IV magnesium should be considered for acute attacks, while oral magnesium may be an alternative for prophylaxis in patients intolerant to first-line treatments.